Demystifying Performance Management Practices on Employee Commitment: Evidence from Tanzania Public Service Organizations - E. L. Tandika (Kelaniya Journal of Management)
This study assessed the impact of Performance Management Practices on employees’ commitment in Tanzania public service organizations. The study was grounded in Goal Setting and Social Exchange theories, which served as the conceptual foundation for interpreting and validating the study's findings. A cross-sectional design with a quantitative approach was employed. Primary data were collected using a structured questionnaire, and the sample comprised 249 respondents randomly selected from 51 public sector organizations in Tanzania. The study employed PLS-SEM to test and estimate causal relationships between variables. The findings indicated a positive and statistically significant influence of the Open Performance Review and Appraisal System (OPRAS) on affective, continuance, and normative dimensions of organizational commitment. It also revealed that proper implementation of OPRAS makes employees develop feelings of being cared, valued and supported, and this creates a feeling of indebtedness among employees through reciprocation that make them committed, therefore work tirelessly to achieve organizational goals.